Numerical investigation of the cold-formed I-beams bending strength with different web shapes - Nadia Kouider; Yazid Hadidane; Mohammed Benzerara (Fracture and Structural Integrity)
The wide use of cold-formed sections (CFS) in the field of steel constructions, favored by the multiple advantages they offer (lightness, ease of installation, etc.), has led us to reflect on a new process for manufacture of metal beams allowing the design of very large span hangars and a reduction in instability problems. This paper presents a study of the theoretical and numerical behavior of a large span CFS beam with different webs, a solid web, a triangular corrugated web, and a trapezoidal corrugated web. These beams are stressed by a concentrated bending load at mid-span. Numerical modeling was done using the finite element software ABAQUS. The numerical results have been validated by the analytical results those obtained based on Eurocode 3. The load capacity and failure modes of the beams were discussed. According to numerical and analytical analysis, corrugated web beams perform better than all other sections.